Le Serment des Horaces face à la satire graphique - Davis, Peggy (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2012)
Between 1815 and 1819, from the fall of the Empire to the second Restoration, a number of caricatures derived from Jacques-Louis David’s 1784 Oath of Horatii were produced. Visually and textually, these prints assert their relationship with the famous picture while using the devices of quotation (the recycling and adaptation of an iconic figure) and parody (the burlesque imitation of a serious work). In addition to confirming the effectiveness and immediate intelligibility of David’s composition, these prints somehow equate to it in their shared goal of revealing an underlying truth, through the exaggeration of caricature. David’s work and the ensuing satirical prints belong, each in their respective historical context, to a culture of opposition. In adapting themselves to dominant culture, they convey it in a new visual language and address a new type of audience in the social arena, sites such as the Salon under the Ancien Régime or the print-shop window under the Restoration. Within the context of the Restoration and the regicidal artist’s political exile, the parodies of the Horatii participate in the critical reception of Davidian aesthetics. Moreover, the caricatures inspired by the Horatii satirize the political and social topics of the day, by delegitimizing the return of reactionary ideology, by denouncing allegiance reversals towards power, or by criticizing superficial civic values. Diverting from the virtuous rhetoric of David’s picture, the caricatures exploit the ironic mode by using antitheses: loyalty and opportunism, luminous reason and obscurantism, martial strength and decrepitude, frugality and gluttony, austerity and bourgeois materialism. It is through the density of allusion to the represented historical moment and to the adopted point of view that intertextuality emerges between the picture of the Horatii and the satirical prints.